Closure of microscopic urethral fistulas by invagination - ناصر, حسان (Latakia University Journal -Medical Sciences Series, 2022)
Study objective :Study of the results of closure of the microscopic inferior urethral nodules by invagination method without excision of the fistula tract methods:A study was conducted over 10 years on 110 cases of hypospadias, where the surgery was performed using duplay technique .We had 14 microscopic urethral fistula cases that were included in the study and the results were evaluated in terms of fistula healing or recurrence. Results :It was good, as there was a cure in 13 out of 14 cases, with a rate of 92.85%, while there was only one failure case that was associated with postoperative sepsis. Conclusion:The method of closing microscopic urethral fistulas by invagination is encouraging, as the cure rate was 92.85% in the cases included in the study.